Legality and Legitimacy: Normative and Sociological Approaches - Thornhill, Chris,; Ashenden, Samantha, (Nomos Verlagsgesellschaft mbH & Co. KG, 2010)
The question about the relation between legality and political legitimacy is both one of the basic questions of modern legal and political philosophy and one of the most important problems in theoretical sociology. This volume brings together the work of a number of internationally prominent legal theorists, political theorists, sociologists, historians and philosophers, all of whom have worked extensively on the conceptual analysis of law and power, in order to address and illuminate this central question of the social sciences. The primary objective of the book is to propose and elaborate paradigms that traverse conventional disciplinary boundaries, and to combine sociological and normative/deductive patterns of analysis in order both to capture the legitimatory foundations of modern societies and accurately to account for the transformation of the classical foundations of political legitimacy in recent decades. All chapters in the volume propose new and challenging paradigms for analyzing the legal sources of legitimate power both in the historical formation of modern societies and in the present. .